RELEVANSI TATA KELOLA PUBLIK DAN ETIKA PERUSAHAAN - Sofik Handoyo (JAF (Journal of Accounting and Finance), 2019)
This study aims to investigate the association of public governance and corporate ethics. Motive of the study was driven by numerous corporate scandals in various countries and practice of good governance both in private and public sector. The study was intended to reveal, whether the country that apply good practice of governance will also lead good practice of corporate ethics in that country. The study adopted exploratory research design which are public governance and corporate ethics proxied as two independent variables. Public governance was represented by attributes namely public accountability, control of corruption, effectiveness government, regulatory quality, rule of law, regulatory quality and political stability. The results show that all public governance attributes are positively and significantly associated with corporate ethics. Pearson correlation coefficient indicates that all attributes of public governance have strong correlation (Pearson correlation (r) > 0.6), except for public accountability attribute. The result implies that the practice of good governance in governmental sector have potential impact on how private sector running their business organizations.